"Building the business model" or "Broadening our international perspectives"? Staff positioning on the values of hosting international students in the Australian school sector. (2022) - Tran, Ly Thi; Blackmore, Jill; Bui, Huyen; Hoang, Trang; Beavis, Catherine; Rowan, Leonie; McCandless, Trevor; Chou-Lee, Manaia; Hurem, Aida
Highlights: The article captures school staff's views about the value of international students It uses positioning theory as a conceptual framework to analyse staff positionings International students can assist to boost schools' symbolic positioning There is a gap between the perceived values of international students and the reality. Abstract: This article focuses on school staff' perspectives about the value of international students. The positioning of international students by the interviewees shows how hosting this cohort can assist to boost schools' symbolic positioning in international education formed by labelling the school as 'culturally diverse', 'inclusive', 'international' and 'global'. But there seems to be a gap between symbolic positioning on the one hand and the capitalization of international students on the other hand as valuable resources to realise the internationalisation of schools. The article provides insights into the perceived values of international students and the barriers to achieving these potential benefits.